Islet allograft rejection can be mediated by CD4+, alloantigen experienced, direct pathway T cells of TH1 and TH2 cytokine phenotype. - Barbara, J; Turvey, SE; Kingsley, C; Spriewald, B; Hara, M; Witzke, O; Morris, P; Wood, K (2000)
BACKGROUND: It is widely believed that Thl cells that secrete interferon-gamma are primarily involved in the rejection of allografts whereas Th2 cells [interleukin(IL) 4 and IL-10] are thought to be protective of this process. However, the exact role and specificity of these helper T lymphocytes in mediating allograft damage is presently unknown. METHODS: Th0, Th1, and Th2 cell lines specific for the class II MHC molecule H2IAb were adoptively transferred into T cell deficient, syngeneic, diabetic mice before transplantation of fully allogeneic C57BL/10 (H2b) or (CBKxBALB/c)F1 (H2k/d+Kb) islet grafts. T cells were 5-(and-6-)-carboxyfluorescein diacetate succinimidyl ester- (CFSE) labeled to allow detection, immunohistochemistry was performed, and IL-4 transcripts within the rejected islet grafts were quantified by reverse transcriptase polymerase chain reaction (RT-PCR). RESULTS: Adoptive transfer (IV) of Th0-, Th1-, and Th2 IAb-specific T cells resulted in rejection of H2b islet allografts. CFSE-labeling demonstrated that these T cells were able to home to the graft site. CD4+ T cells and CD11b+ macrophages were present within the graft after adoptive transfer of both Thl and Th2 cells. Interestingly, CD8+ T cells and B cells were absent from these rejecting grafts. Even when Th2 cells were introduced directly at the graft site, prompt rejection was still observed despite the presence of increased IL-4 mRNA expression within the islet allografts. CONCLUSIONS: Th2 and Th0 alloreactive CD4+ T helper cells can reject islet grafts with similar efficiency to Th1 cells. These results suggest that deviation of the immune response from a Th1 to Th2 phenotype will not be sufficient to allow successful engraftment of allogeneic organs or tissues.